The roles of fasting blood glucose to HDL-cholesterol ratio and monocyte to HDL-cholesterol ratio on coronary slow flow in non-diabetic patients - Sara Cetin Sanlialp; Musa Sanlialp; Gokay Nar; Cennet Yildiz (National Scientific Medical Center, 2021)
Aim: This study aimed to evaluate the relationship between coronary slow flow (CSF) with fasting blood glucose/high-density lipoprotein cholesterol ratio (GHR) and monocyte/high-density lipoprotein cholesterol ratio (MHR) in patients without overt diabetes and to reveal the effects of hyperglycemia and inflammation on CSF development. Material and Methods: In this retrospective study,   a total of 237 patients who underwent coronary angiography were enrolled and divided into two groups according to CSF presence. 109 of them had CSF and 128 of them had normal coronary flow (CNF). The thrombolysis in myocardial infarction (TIMI) frame count (TFC) was calculated for each coronary artery and the values above the normal range was defined as CSF. Results: GHR and MHR were significantly higher in CSF patients compared to those without (p<0.001, p<0.001). In correlation analysis, total TFC showed a statistically significant relation with these markers (for both r=0.745, p<0.001). In multivariate logistic regression analysis, GHR and MHR were independent predictors for CSF presence (p<0.001, p<0.001). The receiver operating characteristic (ROC) curve analysis showed the  best  cut off values of GHR and MHR as 2.105 and as 12.93, respectively (AUC=0.861, p<0.001; AUC=0.849, p<0.001). Conclusion: In this study, there was a strong relationship between CSF with GHR and MHR. In addition, elevated values of GHR and MHR supported the roles of hyperglycemia and inflammation in CSF etiopathogenesis.